ANALISIS KEMAMPUAN MEMBACA SISWA KELAS 1C DI MI NURUL HUDA PANGENAN (DITINJAU) PADA LULUSAN TAMAN KANAK-KANAK - Ovi saqinahtul haq; Siti Rohmah; Jihan Zaeni Syihab; Afiyatun Kholifa (IAIC (Institut Agama Islam Cirebon), 2022)
ABSTRACK Madrasah Ibtidaiyah (MI) or Elementary School (SD) are required so that children are accustomed and trained in letters or numbers so that children will be easier and ready to continue their next level of education. The purpose of this study was to determine the reading ability of grade 1C students at MI Nurul Huda Pangenaan in terms of kindergarten graduates. This research method uses qualitative descriptive technical. The sources of data for this research were interviews and documents. Interviews were conducted with the homeroom teacher of class 1C. The results of this study indicate that 30% of the number of students in class 1C are not fluent in reading. This is based on the background of students who are not graduates of RA or Kindergarten. Thus it can be concluded that graduates of Roudlatul Athfal (RA) or Kindergarten (TK) are able to produce graduates who have good reading skills. So that students who graduate from RA or Kindergarten when receiving students are placed in superior classes or classes that are indeed prepared for further classes. So that both in class placement and reading completeness students are considered capable and can avoid falling behind in class in the future.